Health-Related Quality of Life and Oropharyngeal Dysphagia: A Systematic Review - Jones, E.; Speyer, R.; Kertscher, B.; Denman, D.; Swan, K.; Cordier, Reinie (Springer, 2017)
The negative impact of increased bolus modification on health-related quality of life (HRQoL) in persons with oropharyngeal dysphagia (OD) has been described in previous literature; however, findings may have been influenced by the severity of OD and underlying etiology. The current systematic review therefore aims to investigate the relationships between HRQoL and OD and to report on changes in HRQoL and OD following intervention. This review was conducted in accordance with the PRISMA statement. A systematic search of the literature was performed using PubMed and Embase. All available English publications up to February 2016 that reported on OD and HRQoL were included. Articles that studied OD arising from esophageal dysfunction or included less than 15 participants with OD, were excluded. Thirty-five studies met the inclusion criteria. Inverse bidirectional relationships were found between decreased HRQoL and increased OD severity. Following intervention, changes were evident through improved HRQoL with decreased OD severity. The findings of this paper highlight the importance of targeting HRQoL in patients with OD. However, because of the heterogeneity in methodology, terminology, and assessment procedures used in the retrieved articles, the generalization of study results is limited. More research investigating the relationships between HRQoL and OD is needed. Future studies should implement study designs that lead to stronger levels of evidence, quantify the severity of OD and underlying diseases, use validated measures and less ambiguous terminology.